2006
DOI: 10.1080/07357900500449546
|View full text |Cite
|
Sign up to set email alerts
|

Methylated Tumor-Specific DNA as a Plasma Biomarker in Patients with Glioma

Abstract: Patients with high grade gliomas have large amounts of DNA in the plasma. Of these primary brain tumors, 90 percent contained methylated gene promoters, and in over 60 percent of these patients the same methylated promoters present in the tumor also were found in the plasma. This represents the first step to developing a quantitative plasma biomarker that could be used to monitor glioma status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Techniques such as methyl-BEAMing, methylation-specific PCR, and quantum dot–based fluorescence resonance energy transfer (QD-FRET) have been adapted to detect methylated fragments of DNA extracted from plasma. 78,8486 Much like measuring mutations in ctDNA, methylated DNA fragments from the tumor found in circulation are similar to the degree of methylation in the tumor itself and may also correspond to tumor burden. The overall specificity of measuring methylated DNA is lower as compared with genomic alterations, potentially because of the fact that there are often overlapping methylation changes in the tumor and surrounding normal tissue.…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…Techniques such as methyl-BEAMing, methylation-specific PCR, and quantum dot–based fluorescence resonance energy transfer (QD-FRET) have been adapted to detect methylated fragments of DNA extracted from plasma. 78,8486 Much like measuring mutations in ctDNA, methylated DNA fragments from the tumor found in circulation are similar to the degree of methylation in the tumor itself and may also correspond to tumor burden. The overall specificity of measuring methylated DNA is lower as compared with genomic alterations, potentially because of the fact that there are often overlapping methylation changes in the tumor and surrounding normal tissue.…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…This biomarker may be useful as a source of patient stratification for clinical trials. MGMT status can be identified in tissue and serum from GBM patients [89,90]. …”
Section: Potential Glioma Biomarker Candidatesmentioning
confidence: 99%
“…This epigenetic approach has been used in various cancers such as non-small cell lung cancer,70 head and neck cancers,71 colon cancer72 and glioma73 to develop cancer markers based on promoter hypermethylation. In non-invasive prenatal diagnosis, previous studies have shown that DNA methylation in placental tissues (the major source of fetal DNA in maternal plasma)74 and maternal blood cells (the presumed major source of maternal DNA in maternal plasma)75 are different in many genomic regions 76 – 79.…”
Section: Interpretation Of Negative Results With Confidencementioning
confidence: 99%